Freedom of expression in cyberspace: a study on the acceptance of applying cyber laws in the MSC flagship applications by law and communication professionals - Abdel-Hameed, Adam Mohamed Ahmed (2000)
This study deals with the acceptance of applying cyber laws in the MSC flagship applications by law and communication professionals. It aims at assessing whether the provision of freedom of expression in the Multimedia Super Corridor (MSC) facilitates its flagship applications. determining the extent to which it should be exercised in light of the right to reputation. the right to privacy and the right to decency. comparing the views of the targeted professionals regarding the study issues as well as determining the relationships between selected demographic characteristics and freedom of expression for the facilitation of MSC. freedom of expression and the right to reputation. freedom of expression and the right to privacy and freedom of expression and the right to decency. Data for the study was collected through a self-administered questionnaire developed by the researcher distributed to respondents consisted of law and communication professionals in the Klang Valley area of Malaysia. Two hundred and forty professionals answered the questionnaire. Data collection was conducted during August and September 1999. It is revealed that freedom of expression is favoured for the facilitation of the flagship applications of the MSC, where the responses were very high in this respect. On the other hand, respondents showed concern about other rights. They showed concern about their right to reputation not to be defamed, their right to privacy not to be invaded and their right to decent materials not to be deprived from. Thus they favoured the balancing approach that should be made by the law. As such, the researcher recommended that there should be official efforts toward the awareness of law and communication professionals of the MSC and its applications and objectives. Also, he recommended that the current cyber laws should be amended so as the users will be secured of their reputation, the privacy of the information they provide in the implementation of a certain flagship application and the decency. In addition, he recommended that future formulation of the law should consult those with expertise.